Problems of modern corporate legislation and prospects for its development (Law and Safety, 2025)
With a view to eliminating the gaps and contradictions in current civil legislation and law enforcement practice regarding the determination of the legal forms of legal entities within which corporate relations take place, the article proposes to enshrine the provision according to which the relevant legal relations exist exclusively within a joint-stock company, a limited liability company and an additional liability company.It is proved that one of the directions of development of corporate legislation is to outline the range of fundamental rights and obligations of participants to corporate relations and enshrine them in the Civil Code of Ukraine. Such rights and obligations are understood to be those which are common to all participants (shareholders) of business entities with a corporate structure. At the same time, the Civil Code should contain an indication that certain (specific) rights and obligations of the above persons may be provided for by special legislation, and the mechanism for their exercise may also be provided for by a corporate agreement, if concluded.It is substantiated that the priorities should include consolidation at the level of the Civil Code of Ukraine of the provisions on: a) corporate governance, with details of the provisions on bodies of business entities and their officials who form and express the will of such entities in civil relations; b) corporate control, with regulation of the issues of dependence of one (several) business entity on another (other) entity and the legal consequences of such dependence, including compensation for damage caused to the dependent entity and its participants.The author notes that the tendencies of uniform application of corporate liability rules should be unified by consistent codification of the provisions on liability in relations related to the management of business entities in the Civil Code of Ukraine. Taking into account the practical expansion of the range of persons who may bear corporate liability and the grounds for bringing them to liability, the rules on such liability for all types of business companies should be transferred from special laws and systematised by the provisions of the Civil Code of Ukraine.
Keywords: national and international legislation; protection of rights; court practice; court decision; business company; liability; corporate relations; corporate rights.